Potential of Sorghum Seeds in Alleviating Hyperglycemia, Oxidative Stress, and Glycation Damage - Nora Ben El Mahdi; Laurent Lemée; Quentin Blancart Remaury; Lilian Eloy; Naima Nhiri; Naoufal Lakhssassi; Francesco Cacciola; Mohamed Nhiri (Molecules, 2024)
Diabetes mellitus, characterized by dysregulated glucose metabolism, oxidative stress, and the formation of advanced glycation end products, poses a significant global health burden. In this study, we explored the potential of sorghum (Sorghum bicolor) seeds, known for their abundant phytochemical composition, as a natural remedy for diabetes and its associated damage. High-performance liquid chromatography/high-resolution mass spectrometry analysis revealed a remarkable phenolic richness in sorghum grains, including gallic acid, quercetin, and the predominant procyanidin B-1, with ecotype-specific variations in flavonoid distribution. Elemental analysis by ICP showed an abundance of macro-elements (Ca, K, Mg), trace elements (Fe, Mn, Si, Zn), and ultra-trace elements (B, Co, Cr, Cu, Mo, Se, V) essential for human health, supporting its therapeutic and nutritional potential. Additionally, the results demonstrated variable total phenolic contents (188–297 mg GAE/g dE) and total flavonoid contents (66–78 mg QE/g dE), with corresponding differences in antioxidant activities across the five ecotypes. Treatment with sorghum seed extract (SE1) significantly reduced oxidative stress markers, such as malondialdehyde (MDA)by 40% and hydrogen peroxide (H2O2) by 63%, in diabetic mice, compared to untreated diabetic controls. Moreover, sorghum extracts exhibited a remarkable increase in antioxidant enzyme activities, including a 50% increase in superoxide dismutase (SOD) activity and a 60% increase in glutathione peroxidase (GPx) activity, indicating their potential to bolster antioxidant defenses against diabetes-induced oxidative stress. These findings underscore the therapeutic potential of sorghum seeds in diabetes management and prevention, paving the way for the development of functional foods with enhanced health benefits.